1999
DOI: 10.1089/ees.1999.16.147
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Seawater on the Dissolution Potential of Phosphogypsum:Cement Composites

Abstract: Polarized optical microscopy, scanning electron microscopy, and X-ray microprobe analysis were used to investigate the effect of seawater on phosphogypsum (PG):cement composites. Thin surface sections were taken from 85%: 15% PG:cement composites that had been submerged under natural seawater conditions for 1 month and 70%:30% PGicement composites that had been submerged under natural seawater conditions for 1 year. The optical microscopy results revealed a crystalline layer of carbonates on the surface of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Conversely, the cement content must remain low enough to maintain the economic feasibility of such an approach. Recent studies have indicated the presence of a calcium carbonate coating on the surface of composites that showed no signs of deterioration following saltwater submergence (2). Calcium carbonate requires high pH conditions to form.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the cement content must remain low enough to maintain the economic feasibility of such an approach. Recent studies have indicated the presence of a calcium carbonate coating on the surface of composites that showed no signs of deterioration following saltwater submergence (2). Calcium carbonate requires high pH conditions to form.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion Model. Other research by Guo et al (11) indicates that the reactants (Ca 2+ and CO3 2-) for the formation of the CaCO3 coating originated from saltwater and not from the PG composite. Thus, Ca 2+ release from the PG composite can be considered nonreactive.…”
Section: Methodsmentioning
confidence: 90%
“…Initial research showed PG composites that remained physically intact after submergence in saltwater contained a calcium carbonate coating. Conversely, this coating was absent in severely degraded composites (11).…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations